2017
DOI: 10.1177/2309499017739499
|View full text |Cite
|
Sign up to set email alerts
|

Perceived comfort during minor hand surgeries with wide awake local anaesthesia no tourniquet (WALANT) versus local anaesthesia (LA)/tourniquet

Abstract: WALANT technique was associated with better patient comfort. Tourniquet was the main reason for discomfort during surgeries. WALANT is an alternative in minor hand surgeries for a bloodless surgical field without the discomfort of tourniquet application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 17 publications
2
68
0
6
Order By: Relevance
“…Thus, a wide-awake local anesthesia with no tourniquet procedure was developed. The WALANT technique has been used in different hand surgeries, particularly in soft tissue repair or reconstruction [ 1 , 16 20 ]. In addition, finger fractures could be also treated by closed reduction and percutaneous pinning under WALANT technique [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a wide-awake local anesthesia with no tourniquet procedure was developed. The WALANT technique has been used in different hand surgeries, particularly in soft tissue repair or reconstruction [ 1 , 16 20 ]. In addition, finger fractures could be also treated by closed reduction and percutaneous pinning under WALANT technique [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Iqbal et al (14) published a study in 2018 in which they randomized Carpal tunnel release cases to undergo either local anesthesia plus adrenaline or local anesthesia plus tourniquet and they found that early pain score was significantly higher in the latter group. Gunasagaran et al (15) compared WALANT technique to local anesthesia plus tourniquet in 72 cases with minor hand surgery and they reported lower early postoperative pain in subjects undergoing WALANT technique. Consistent with the literature, our findings may be attributed the prolongation of postoperative analgesic time with adrenaline and/or aggravation of postoperative pain level by tourniquet application.…”
Section: Discussionmentioning
confidence: 99%
“…Other advantages of the technique include avoidance of tourniquet-related pain and other complications and evaluation of perioperative active movements via patient cooperation. Finger fracture fixation, tendon repair or transfer, arthrodesis, arthroplasty, release of median nerve and trigger finger could be performed with this technique (15). In this study, we performed open median nerve release with this technique.…”
Section: Discussionmentioning
confidence: 99%
“…The study, however, involved different procedures on a variety of cases such as carpal tunnel, trigger finger, and ganglion. 5…”
Section: Introductionmentioning
confidence: 99%
“…12 Usage of tourniquet causes intraoperative pain to patients; hence, with this new practice where a tourniquet is not required, one can be more comfortable doing the surgery without the risks and pain of tourniquet, resulting in a better patient experience. 5,13…”
Section: Introductionmentioning
confidence: 99%